Valorizing time as a civilizational asset: glimpses into the views of Malik Bennabi and Said Nursi - Berghout, Abdul Aziz (International Islamic University Malaysia (IIUM), 2016)
This paper examines the notion of time not only as an interval or period or unit of measurement made of seconds, minutes, hours, days, weeks, months and years, but essentially as a civilizational and spiritual asset. We need to valorize time as a source of civilizational progress and development. Time is seen as a value and a source of civilizational activity leading to progress and socio-cultural development. Our understanding, appreciation and utilization of time will partly depend on our perspective of life itself be it temporal or eternal. How our worldviews articulate the notion of time bears heavily on our action and dynamism in history and life. Our worldview will make the notion of time a civilizing power and a place for added value and progress or a way to decline. This paper addresses the question of civilizational and spiritual value of time stressing the need for educating people about time as a wealth that is crucial in their self and collective development and progress. It examines the notion of time as a civilizational asset that adds value to the life and development of the individual and society as well. A special reference will be made to selected views of both Malik Bennabi (1905-1973) and Said Nursi (1878-1960), who might be considered among the pioneering Muslim thinkers, who studied the notion of time reflecting on its civilizational and spiritual dimensions. The paper concludes that both scholars have made important contribution to the study of time from an Islamic perspective. While Malik Bennabi underscores the civilizational and social aspects of time, Said Nursi stresses the importance of metaphysical, spiritual and moral aspects of time. This paper also shows that the Quranic view of time is more comprehensive and all-encompassing.